The Distribution of Sport Performance Gene Variations Through COVID-19 Disease Severity - Yenmis, Guven; Kallenci, Ilayda; Dokur, Mehmet; Koc, Suna; Yalinkilic, Sila Basak; Atak, Evren; Demirbilek, Mahmut; Arkan, Hulya (MDPI, 2025)
Background/Objectives: Since its emergence in 2020, researchers worldwide have been collaborating to better understand the SARS-CoV-2 disease's pathophysiology. Disease severity can vary based on several factors, including comorbidities and genetic variations. Notably, recent studies have highlighted the role of genes associated with athletic performance, such as ACE, ACTN3, and PPARGC1A, in influencing muscle function, cardiovascular health, and the body's metabolic response. Given that these genes also impact oxidative metabolism, inflammation, and respiratory efficiency, we hypothesized that they might play a critical role in the host's response to SARS-CoV-2 infection. This study aimed to investigate the association between disease severity and genetic polymorphisms in these sport performance-related genes, specifically ACE rs4646994, ACTN3 rs1815739, and PPARGC1A rs8192678. Methods: A total of 422 COVID-19-positive patients were included in this study. The participants were divided into three groups: a severe group (77 patients) requiring intensive care unit (ICU) admission, a mild group (300 patients) exhibiting at least one symptom, and an asymptomatic control group. Genotyping was performed using restriction fragment length polymorphism PCR. Results: The D allele and DD genotype of ACE and the T allele and TT genotype of ACTN3 were found to confer protective effects against severe SARS-CoV-2 infection. Conversely, the PPARGC1A TC genotype and the ACE-PPARGC1A ins/ins + TC combined genotype were associated with increased disease severity (p < 0.05). Conclusions: Although vaccination has reduced the severity of SARS-CoV-2, the virus continues to impact human health. Inter-individual differences due to these genetic variations will broaden the horizon of knowledge on the pathophysiology of the disease.
Keywords: COVID-19; biomarkers; ACTN3; ACE; PPARGC1A; intensive care unit; disease severity; TRANSCRIPTIONAL COACTIVATOR; ALPHA-ACTININ-3 DEFICIENCY; ACTN3 GENOTYPE; HEPATIC GLUCONEOGENESIS; POLYMORPHISM; METAANALYSIS; PGC-1-ALPHA; PGC-1; SUSCEPTIBILITY; General & Internal Medicine